Laser-induced fluorescent diagnostics of dental caries - Voropay, Eugene S.; Samtsov, Michael P.; Lyashenko, Lyudmila S.; Butvilovsky, Alexandr V.; Haifulina, Viktoriya R.; Bobkova, Maria V. (Journal of the Belarusian State University. Physics, 2017)
This paper presents the results obtained in vitro in studies of the spectral and luminescence characteristics for the surfaces of hard dental tissues in the norm and with pathologies when using for radiation excitation the laser sources with the wavelength l = 514.5 or l = 684 nm. It is shown that, on excitation by an argon laser with l = 514.5 nm, a maximum of a fluorescence spectrum for the normal dental tissue is located at 568 nm, the band halfwidth coming to 122 nm. A maximum of fluorescence for the caries affected dental area is found at the wavelength l = 655 nm, the halfwidth coming to 192 nm. It is demonstrated that, with the use of a spectrometric system using radiation of a semiconductor laser with the wavelength 684 nm for fluorescence excitation, the form and position of fluorescence spectra for carious tissues is identical to that for the normal tissues (with a maximum at 755 nm at the halfwidth 75 nm) but the fluorescence intensity is higher by the order of magnitude. It is found that, on excitation at the wavelength 684 nm, there is a possibility to reveal not only the surface but also the deep-lying caries. The data obtained point to the effectiveness of the proposed laser-induce fluorescence method for diagnostication of dental caries owing to the realization of optical probing of dental health.
Keywords: enamel; caries; hard dental tissues; laser-induced fluorescence; diagnostics